The Correlation of Mother's Age with Types of Labor on Maternity Mothers in Patut Patuh Patju West Lombok Hospital - Linda Azizah; Sastrawan; Sabar Setiawan (Science Midwifery, 2022)
Background: Age is considered important because it determines the prognosis in childbirth, because it can cause pain (complications) for both mother and fetus. Pregnancy At the age of less than 20 years will be easier to experience complications, in the age group over 35 years is 3 times higher than the healthy reproductive age group (20-35 years). Methods: This research design is a cross sectional study. The population of this study were all mothers who gave birth at the Patut Patuh Patju Hospital, West Lombok for the period of January 1 to June 30 in 2020 as many as 2,503 people. The sampling technique used is simple random sampling, with a total sample of 345 people. Data analysis using Chi Square analysis.Results: The age of the mother who gave birth at the Patut Patuh Patju Hospital, West Lombok, was mostly of healthy reproductive age, ie 20-35 years by 72.8%. The type of delivery in the mothers who gave birth at the Patut Patuh Patju Hospital, West Lombok, the majority of mothers who gave birth normally, amounted to 60.6%. The results of the analysis obtained that the value of X2count is smaller than X2tabe1 (2.360<5.591) and the p-value of 0.307 The contingency coefficient (t) is 0.08. Conclusion: There is no relationship between maternal age and type of delivery in mothers who give birth at Patut Patuh Patju Hospital, West Lombok for the period January 1 to June 30 2016..